Chapter Fostering Personal Knowledge and Competences in Higher Education Guidance Processes - Bellantonio, Sergio (Firenze University Press, 2022)
Education is a constantly ongoing process that allows individuals to interpret and transform reality. The variety of life contexts, formal, non-formal or informal, are explicitly or latently involved in this process and contribute decisively to building a personal knowledge and competence system at the basis of subjectivity. The aim of this paper is to highlight the role played by knowledge and competence arising from personal experience within profiles of professional competences, to implement possible reflective paths in higher education guidance processes